Effect of nitrogen fertilization and fungicidal sprays on blast and yield of upland rice - Faria, Josias Corrêa de; Prabhu, Anne Sitarama; Zimmermann, Francisco José P. (Pesquisa Agropecuaria Brasileira, 2014)
The influence of nitrogen fertilization and fungicidal sprays on blast and rice yield was studied for optimum utilization of the inputs under upland conditions. During 1976/78, two field trials were conducted with the cultivar IAC 41 using five levels of nitrogen including control (0, 15, 30, 45 and 60 kg/ha in the form of ammonium sulphate) and 0, 1 and 2 sprays of benomyl (250 g/ha), in all combinations. The results demonstrated that leaf blast as well as neck and panicle blast increased with the increase in nitrogen level. The ocurrence of prolonged drought periods and heavy blast incidence reduced the yield when nitrogen was applied over 15 kg/ha at planting time with or without the use of fungicide. The relationship between the yield and nitrogen level was quadratic, indicating the yield reduction under water stress conditions.